Hearing and music in unilateral spatial neglect neuro-rehabilitation - Guilbert, Alma; Sylvain Clément,; Moroni, Christine (Frontiers in Psychology, 2014)
Unilateral Spatial Neglect (USN) is an attention deficit in the contralesional side of space which occurs after a cerebral stroke, mainly located in the right hemisphere. USN patients are disabled in all daily activities. USN is an important negative prognostic factor of functional recovery and of socio-professional reinsertion. Thus, patient rehabilitation is a major challenge. As this deficit has been described in many sensory modalities (including hearing), many sensory and poly-sensory rehabilitation methods have been proposed to USN patients. They are mainly based on visual, tactile modalities and on motor abilities. However, these methods appear to be quite task-specific and difficult to transfer to functional activities. Very few studies have focused on the hearing modality and even fewer studies have been conducted in music as a way of improving spatial attention. Therefore, more research on such retraining needs is neccessary in order to make reliable conclusions on its efficiency in long-term rehabilitation. Nevertheless, some evidence suggests that music could be a promising tool to enhance spatial attention and to rehabilitate USN patients. In fact, music is a material closely linked to space, involving common anatomical and functional networks. The present paper aims firstly at briefly reviewing the different procedures of sensory retraining proposed in USN, including auditory retraining, and their limits. Secondly, it aims to present the recent scientific evidence that makes music a good candidate for USN patients’ neuro-rehabilitation.